FORMATION OF INVESTMEN POTENTIAL FOR ENERGY CONSERVATION MEASURES IN THE SOCIAL SPHERE OF UKRAINE - Stavnycha , N.I. (The actual problems of regional economy development, 2017)
The article is devoted to searching for sources of investment for measures of energy supply in the social sphere. The aim of the article is to determine possible resources for their attraction to energy conservation measures in budgetary institutions of the country. To achieve this next methods were used: theoretical generalization, abstract logical analysis, comparison. The results of the research are: isolating of problems in terms of energy efficiency, which take place in budgetary institutions; measures to implement the potential of energy conservation; search sources of investment were proposed. Scientific novelty identify tools that can be sources of investment. The practical significance of the results is that the proposed investment sources can be used in practice by the heads of budgetary institutions in the implementation of energy conservation measures.